2019
DOI: 10.3390/su11061583
|View full text |Cite
|
Sign up to set email alerts
|

Government R&D Subsidy and Additionality of Biotechnology Firms: The Case of the South Korean Biotechnology Industry

Abstract: Government research and development (R&D) subsidies are more important in countries that are latecomers to the biotechnology industry, where venture capital has not been developed, and the ratio of start-ups is high. Previous studies have mostly focused on the additionality of the input and output through government R&D subsidies, such as private R&D investment, technological innovation, and financial performance. In addition, some studies have focused on the behavioral additionality (the change in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 90 publications
(159 reference statements)
1
18
0
1
Order By: Relevance
“…This is because venture capital markets in latecomer countries such as Korea or China are not mature enough, so investment funds are often not supplied in time. Research has found that firms that receive government R&D support benefits have a higher survival rate and have a positive effect on R&D strength and technological innovation performance than those that do not [72]. In particular, corporate managers and doctors need to cooperate for joint research and development, and medical device patent applications also need to be submitted in collaboration with doctors' ideas and firm technical resources [1,2,73].…”
Section: Discussionmentioning
confidence: 99%
“…This is because venture capital markets in latecomer countries such as Korea or China are not mature enough, so investment funds are often not supplied in time. Research has found that firms that receive government R&D support benefits have a higher survival rate and have a positive effect on R&D strength and technological innovation performance than those that do not [72]. In particular, corporate managers and doctors need to cooperate for joint research and development, and medical device patent applications also need to be submitted in collaboration with doctors' ideas and firm technical resources [1,2,73].…”
Section: Discussionmentioning
confidence: 99%
“…The identification of good investment opportunities may be difficult in the biotechnology sector in which firms bear large research and development costs and take on scientific risks that become increasingly dependent on (1) the type of drug that firms develop and bring to the market and (2) the state of the economy [10,17]. The cost of biopharmaceutical treatments is much higher than that of using small-molecule treatments [18,19], due to the large failure rates in clinical trials and the long development process period, both of them contributing to increasing the drug prices [20]. This disparity in drug prices decreases when the patent of biopharmaceutical products expires and similar biotherapeutic products appear in the market [21], while orphan drugs are too expensive to develop, requiring governments to provide firms with market exclusivity and public funding in order to recoup the firm's initial investments, to reduce the high financial costs taken on by firms, and to ensure fair and equal access to treatments by patients [17].…”
Section: Literature Review and Development Of Hypothesesmentioning
confidence: 99%
“…These advantages are directly related to competitiveness in the market. Therefore, if the government supports the certification project of food SMEs, it can be expected to produce a significant behavioral additionality effect [126].…”
Section: Discussionmentioning
confidence: 99%